Data from: Caribou avoiding wolves face increased predation by bears – caught between Scylla and Charybdis - Leblond, Mathieu; Dussault, Christian; Ouellet, Jean-Pierre; St-Laurent, Martin-Hugues (Zenodo, 2017)
1. Prey may trade off resource acquisition with mortality risk by using various habitat-selection strategies. Empirical assessments have shown that the functional and numerical responses of predators to human disturbances are variable, yet spatial changes in predation risk by two predators have seldom been studied for prey occurring in human-modified landscapes. Using the boreal caribou (Rangifer tarandus caribou) – grey wolf (Canis lupus) – black bear (Ursus americanus) system in eastern Canada, we investigated whether responses of prey towards one predator could concomitantly increase risk of predation from another predator exhibiting a different foraging tactic. 2. We investigated trade-offs made by solitary caribou females and mothers accompanied by their calf during the period of highest calf vulnerability, and compared the behaviour of mothers that would eventually lose their calf to predation to that of mothers whose calf survived until the following year. We modelled habitat selection using different metrics of forage based on field measurements and digital maps, and developed empirical models of predation risk and prey behaviour using GPS data collected on both predators and prey. 3. Mothers accompanied by their calf seemed to compromise foraging opportunities for safety, as opposed to solitary females who showed no particular avoidance of areas used by predators. Although caribou mothers adopted selection strategies that could have protected their offspring from wolves, females that eventually lost their calf to predation selected for vegetative associations that were favourable to bears. 4. Synthesis and applications. We determined that mothers that most strongly avoided suitable wolf habitat were also those that most strongly selected suitable bear habitat, suggesting that by using anti-predator strategies aimed at reducing predation risk from wolves, caribou exposed their offspring to increased predation risk from bears. This result is of paramount conservation value as bears were responsible for ...